From isolated to 2D coordination polymers based on 6-aminonicotinate and 3d-metal ions: towards field-induced single-ion-magnets. Issue 16 (6th April 2017) - Rodríguez-Diéguez, Antonio; Pérez-Yáñez, Sonia; Ruiz-Rubio, Leire; Seco, Jose M.; Cepeda, Javier
Abstract : The capacity of 6-aminonicotinate to arrange magnetically isolated first-row transition metal ions into a diversity of crystal architectures of six new compounds is studied, revealing best-in-class slow magnetic relaxation for cobalt(ii ) based coordination polymers. Abstract : We report herein the synthesis and structural and chemical characterization of six new compounds consisting of 6-aminonicotinate (6ani) ligands and first-row transition metal ions, namely, [Mn2 (μ-6ani)2 (H2 O)8 ](6ani)2 (1 ), [Co(6ani)(bipy)2 (H2 O)3 ](6ani)·5H2 O (2 ), [M(μ-6ani)(6ani)(H2 O)3 ]·2H2 O [M II = Co (3 ), Ni (4 )], and [M(μ-6ani)2 ]·H2 O [M II = Co (5 ), Cu (6 )] (where bipy = 4, 4′-bipyridine). Compounds1 and2 consist of isolated dimeric and monomeric entities held together by supramolecular interactions governed by 6ani free anions. The rigid and low symmetry of 6ani ligands, in addition to their coordination as terminal and bridging ligands to octahedral metal geometries, gives rise to chiral 1D chains of compounds3 and4 . 2Dsql layers are formed (5 and6 ) when 6ani ligands act as ligands bridging the metal ions, which precludes the presence of water molecules in the framework. Despite the wide structural diversity observed, all architectures share the occurrence of magnetically isolated 3d metal ions, given the poor exchange achieved through 6ani bridges, as confirmed by dc susceptibility measurements and DFT calculations. Dynamic ac susceptibility measurements reveal best-in-class field-induced slow magnetic relaxation behaviour in Co-based compounds with easy-plane magnetic anisotropy. The effective energy barriers ( U eff ) of 39.6 K and 18.7 K for3 and5, respectively, estimated using the Arrhenius law are remarkably high among Co II -SIM coordination polymers reported so far.